Sistem Pemberian Reward Karyawan Dengan Pembobotan AHP dan MOORA pada CV. Putra Karya Logam Sukses - Venty; Riki Andri Yusda; Akmal (Institut Teknologi Garut, 2026)
Determining objective employee rewards is a challenge for manufacturing companies because manual processes are prone to subjectivity and inconsistencies in evaluation. This study aims to develop a Decision Support System based on the integration of the Analytic Hierarchy Process (AHP) and MOORA to improve the accuracy and transparency of performance evaluations. AHP is used to determine the weights of five criteria through a consistency test (CR < 0.1), while MOORA is used for the ranking process of 69 employee alternatives. The results show that the system produces the best alternative with the highest preference value of 0.1474 and demonstrates ranking stability based on a weight sensitivity test (correlation coefficient 0.92). A comparison with the SAW and TOPSIS methods demonstrates the consistency of the best alternative; however, the AHP–MOORA approach provides more structured weight validation and better ranking stability. Scientifically, this study confirms the superiority of integrating weighting and optimization methods in producing a robust and verified decision-making model, particularly in the context of employee reward evaluation in the manufacturing sector.